Salvage surgery for locally recurrent oropharyngeal cancer. (15th July 2015) - Patel, Samip N.; Cohen, Marc A.; Givi, Babak; Dixon, Benjamin J.; Gilbert, Ralph W.; Gullane, Patrick J.; Brown, Dale H.; Irish, Jonathan C.; de Almeida, John R.; Higgins, Kevin M.; Enepekides, Danny; Huang, Shao Hui; et al.
ABSTRACT: Background: There are limited data on whether recurrent human papillomavirus (HPV)‐associated oropharyngeal squamous cell carcinoma (SCC) is associated with higher surgical salvage rates. The purpose of this study was to determine the success rate of salvage surgery for locally recurrent oropharyngeal cancer and factors influencing the outcome, including p16 status. Methods: All patients who underwent salvage surgery for locally recurrent or persistent oropharyngeal cancer after (chemo)radiotherapy between 2000 and 2012 were included. The Kaplan–Meier analysis was used to determine overall survival (OS) and recurrence‐free survival (RFS). Univariable analysis was performed using Cox proportional hazards regression. Results: Thirty‐four patients underwent salvage surgery. Five patients (14.7%) were tracheostomy dependent and 22 (64.7%) were gastrostomy tube dependent after salvage surgery. Postoperative complications occurred in 15 patients. RFS after salvage surgery was 28% and 19% at 3 and 5 years, respectively. The presence of nodal disease at the time of local recurrence, close or positive margins, and lymphovascular invasion were the only factors associated with worse survival on univariable analysis. HPV status based on p16 testing was not associated with either OS or RFS. Conclusion: Surgical salvage for oropharyngeal SCC after failure of radiotherapy (+/‐ chemotherapy) is feasible. Patients who may benefit from surgery include those without regional recurrence and/or those in whom negative margins can be obtained. However, patients may be tracheotomy or gastrostomy tube dependent. The p16 status did not seem to have prognostic impact in the salvage setting; however, larger series are required to assess this relationship. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E658–E664, 2016